Effect of mach number in a suddenly expanded flow for area ratio 4.84 - Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Rathakrishnan, E. (IJERA, 2012)
The experiments were carried out to assess the effect of Mach number on base pressure and control effectiveness in a suddenly expanded duct. In the present study the Mach number at the nozzle exit and the nozzle pressure ratio (NPR) are the flow parameters considered. The area ratio (i.e. ratio between cross sectional area of the sudden expansion duct and the nozzle exit area) and the length-to-diameter ratio of the duct are the geometrical parameters considered. The jet Mach numbers at the entry to the suddenly expanded duct, studied are 1.87, 2.2 and 2.58. The nozzle pressure ratio (NPR) used is from 3 to 11, in steps of 2 and experiments are conducted for NPR 3, 5, 7, 9, and 11 for all the Mach numbers. The area ratio of the present study is 4.84. The L/D ratio of the duct is varied from 10 to 1. Active control in the form of four micro jets of 1mm orifice diameter located at 900 intervals along a pitch circle diameter of 1.3 times the nozzle exit diameter in the base region are employed. In addition to base pressure, wall pressure field along the duct is also studied. From the present studies it is found that for the given area ratio the base pressure increase with Mach number. When the flow is over expanded the base pressure assumes very high value due the presence of oblique shock at the nozzle lip. It is also found from wall pressure studies that the micro jets do not disturb the flow field in the enlarged duct.